Providers' Involvement of Parents, Families, and Family Dynamics in Youth Weight Management Programs - Keeley J. Pratt PhD; Joseph A. Skelton MD; Ihuoma Eneli MD, MS; David N. Coliler MD, PhD; Suzanne Lazorick MD, MPH (SAGE Publishing, 2018)
Family-based interventions are the current standard for the treatment of pediatric obesity, yet the details of how providers are involving family members, and the barriers to family involvement, are largely unknown. The objective of this study is to describe how providers in pediatric weight management (PWM) involve family members, identify barriers to family involvement, and how they address challenging family dynamics. A cross-sectional survey was administered to PWM centers/clinics and their providers in the United States and Canada. Analyses included descriptive statistics at the participant (N = 71) and clinic/center (N = 47) levels. Providers indicated that they assessed patients and parents' perspectives, not other family members, motivation, weight/medical history, dietary and activity behaviors, goals, and barriers. Providers also reported that they asked patients' perspectives about their parents' aforementioned behaviors, and siblings' dietary, activity, and sedentary/screen time behaviors, and weight/medical history. Providers reported that the balance between the patient and parent changed as children aged, with more focus given to the child, and less to the parent, as the child grew older. The most frequent barrier to involving family members in treatment included challenging family dynamics. The most challenging family dynamics were divorce/separation and parent-child conflicts. Providers often refer to and rely on mental/behavioral health providers to address barriers to family involvement and challenging family dynamics. Further research is needed to determine adequate provider training and comfort in dealing with family dynamics in treatment, and ways to mitigate barriers to involving families in PWM.